Aplicacion de riego al frijol de acuerdo con las diferentes fases de desarollo - Díaz D, A.; Castillo, J.J. (International Center for Tropical Agriculture, 1981)
The effect of irrigating by gravitation on yields of bean var. ICA-Palmar, applied during different growth stages,was studied. A randomized block design was used with 7 replications and 7 treatments in an area of 1.5 ha with furrows at 0.60 m (240,000 plants/ha). The system of irrigating by gravitation using gated pipes was utilized. Agronomic practices were done for pest and disease control. Rainfall during the crop cycle modified the treatment. Treatments II, V, and VI used a water depth of 262, 275, and 287 mm and yielded 1874, 1872, and 1831 kg/ha, resp. Treatments I and III used 239 and 231 mm and produced 1652 and 1520 kg/ha, resp. The control only yielded 689 kg/ha and received only 175 mm with irrigation at germination and rainfall during the crop cycle. It was concluded that: (1) Five waterings supplying an usable water depth of 270 mm (an applied water depth of approx. 350 mm) gave the highest bean yield. (2) Irrigation at germination up to a depth of 30 cm allows the crop to develop until 20 days after planting. (3) During flowering (28-30 days) and fructification (48- 50 days) soil moisture tension should not be higher than 35 centibars. (CIAT)